Ancient Wooden Trap from the Moss of Auquharney, Aberdeenshire - Reid, R W (Proceedings of the Society of Antiquaries of Scotland, 1922)
The trap was found in peat and comprises a body made of alder, a movable flap or door made of birch, a bow and two pegs made of willow. With the exception of a horn of Bos Longifrons found 300 feet away no other artefacts were found. The construction is practically identical with twelve univalvular wooden traps found in Ireland and Wales.